PELAKSANAAN ASPEK BAURAN PROMOSI PADA STMIK MARDIRA INDONESIA, BANDUNG - Ali Mulyawan; . Komarudin (Jurnal Computech & Bisnis (e-Journal), 2015)
This research is to describe the implementation aspects of the promotional mix done by STMIK Mardira Indonesia, Bandung. Promotional mixes analyzed include advertesing, personal selling, sales promotion, public relations and direct marketing. A method of analysis using descriptive analysis to obtain an overview of the promotional mix is done. Respondents in this study were students D3 STMIK Mardira Indonesia, Bandung. The result showed that the implementation of the promotion mix is adequate with the highest value of the ideal score is sales promotion. Keyword: Advertesing, Personal selling, Sales Promotion, Public relation, Direct Marketing